(3GdPNjQI aj aQhY GdMfajIs - (3HQgGf GdOjf eMehO Hf CMeO Hf YHO GdYRjR Hf YeQ GdHNGQjs; (3GdeQZjfGfj , eMehO Hf CMeO Hf YHO GdYRjR Hf YeQ Hf eGRg, HQgGf GdOjf,J (B616 (3g` s
(3ChdgG (B:s
(3cJGH GdYJGb s
(3BNQgG (B:s
(3jfJgi BNQ cJGH GdSQbI s
(3GdfSNI HgG MhGTs
(3ef GdfSNI GdSGHbIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
Keywords: (3Gdabg GdMfajs